The supplementary investigation and the violation of the principles of autonomy of the prosecutorial role, judicial impartiality and the right of defense (SCIÉNDO INGENIUM, 2021)
It was investigated how the conduct of the supplementary investigation affects the criminal proceedings initiated in the Superior Court of Justice of La Libertad, period from 2017 to 2019. To achieve the objectives of the investigation, a study sample was considered, the 129 Resolutions issued by the Trujillo Preparatory Investigation Courts in the referred period, selecting 6 resolutions, through simple random sampling. In addition, the national jurisprudence constituted by 4 resolutions of the Superior Court of Justice of 2012-2019; and the I Criminal Jurisdictional Plenary of Huancavelica of 2017; as well as 100 criminal lawyers from Trujillo to gather information on the study variables. The techniques of documentary analysis applied to jurisprudence were used; and the survey applied to criminal lawyers. The information obtained was statistically processed and the results were discussed with the general methods of Science and particular of Law. It was determined that the supplementary investigation ordered by the court infringes said constitutional principles and guarantees, for which the corresponding legislative amendment is proposed, defining its application.
Keywords: The accusatory criminal process; Supplementary investigation; Judicial Impartiality; Fiscal Autonomy; Right of defense